Digital Rehabilitation Interventions for Musculoskeletal Disorders: Clinical Effectiveness and Implementation Challenges - Bajek, Wiktoria; Falana, Joanna; Łydka, Maciej; Machała, Iga; Łaciak, Julia; Libudzic, Natalia; Lichtarska, Kinga; Granatowski, Piotr; Lewandowska, Justyna; Gwóźdź, Anna (Quality in Sport, 2026)
Background: Telerehabilitation has emerged as a promising model of care in the physiotherapy of musculoskeletal disorders due to its accessibility, convenience, and potential to reduce the burden associated with travel. However, it remains unclear to what extent telerehabilitation can replace face-to-face treatment and which patient groups may derive the greatest clinical benefit from this approach. Aim: The aim of this review was to assess the effectiveness, safety, and clinical usefulness of telerehabilitation in selected musculoskeletal disorders. Methods: A comprehensive literature search for this review was conducted at PubMed and Google Scholar to identify studies evaluating the use of telerehabilitation in selected musculoskeletal disorders. A total of 18 studies were thoroughly screened and applied in this literature review due to its accuracy. Results: The reviewed evidence indicates that telerehabilitation is in most cases comparable or non-inferior to in-person physiotherapy in selected musculoskeletal disorders.. The most favorable outcomes were observed in interventions that preserved the key components of rehabilitation, including a structured exercise program, therapist supervision, treatment progression, and regular follow-up. Across the included studies, improvement was reported primarily in pain, functional performance, and selected patient-reported outcomes. A proper safety and acceptability of this form of therapy was confirmed, while serious adverse events were reported rarely or not at all. Conclusions: Telerehabilitation appears to be a valid and clinically useful rehabilitation option in selected musculoskeletal disorders. Its effectiveness seems to depend more on therapeutic structure and professional supervision than on remote delivery alone. Further multicenter studies are needed to define diagnosis-specific indications and identify patients most likely to benefit from this model of care.